Delivering telemedicine consultations for patients with transient ischaemic attack during the COVID‐19 pandemic in a comprehensive tertiary stroke centre in the United Kingdom. (8th February 2021) - D'Anna, Lucio; Ellis, Natalya; Bentley, Paul; Brown, Zoe; Halse, Omid; Jamil, Sohaa; Jenkins, Harri; Malik, Abid; Kalladka, Dheeraj; Kwan, Joseph; Venter, Marius; Banerjee, Soma
Abstract: Background and purpose: The global COVID‐19 pandemic led many stroke centres worldwide to shift from in‐person to telemedicine consultations to assess patients with transient ischaemic attacks (TIAs). We aimed to investigate the impact of telemedicine during the COVID‐19 pandemic on the management and outcome of the patients with TIA. Methods: We retrospectively analysed data from a registry of consecutive TIA patients assessed at the Stroke Department, Imperial College Health Care Trust, London, during the national lockdown period (between March 23 2020 and 30 June 2020). As controls, we evaluated the clinical reports and stroke quality metrics of patients presenting to the TIA clinic in the same period of 2019. Results: Between 23 March 2020 and 30 June 2020, 136 patients were assessed using the telemedicine TIA clinic, compared to 180 patients evaluated with face‐to‐face consultation in the same period in 2019. Patients' characteristics were similar in both groups. At 3 months after the TIA, there were no significant differences in the proportion of patients admitted to the hospital for recurrent TIA/stroke or any other cardiovascular cause from the 2020 period compared to the same period in 2019. Conclusions: Our analysis showed that during the pandemic, our telemedicine consultations of TIA patients were not associated with an increased 3‐month rate of recurrent TIA/stroke or cardiovascular hospital admissions. More robust studies looking at this model of care will be needed to assess its long‐term effects on patients and health care systems.